An IoT-based Smart Security Locker System with OTP Verification - Paneru, Biplov; Shah, Krishna Bikram; Paneru, Bishwash (Journal of ISMAC, 2023)
Due to frequent movements and hangouts between classrooms and office buildings, students’ personal items/expensive gadgets can get lost, misplaced and stolen, this has become a common issue that people across the campus and offices have been frustratingly dealing with. Keeping this in mind, this research work aims to implement a cost-effective “Password-Based Locker Security System” to protect the personal assets of students and staff, like laptops, gadgets, keys, and personal documents. The study presents a prototype security locker that utilizes Arduino UNO connected with a Wi-Fi module, which controls the complete processes like taking a password from the keypad module, comparing passwords, driving the buzzer, triggering the relay, and sending status to the LCD and connecting to the Internet of Things (IoT). The system is based on IoT technology using the Blynk IoT platform, which sends a notification alert to the connected device in case of security breaches. One Time Password (OTP) verification can be done to reset the password after three wrong password inputs. The proposed system is portable, durable, and installable in specific places.
Keywords: Password-Based Locker Security System; Campus Security; Personal Asset Protection; IoT-enabled Security System; Arduino-based Security.